Innovate or game over? Examining effects of product innovativeness on video game success - Franziska Handrich; Sven Heidenreich; Tobias Kraemer (Electronic Markets, 2022)
Abstract In recent years, the video game industry has invested significant amounts in the development of innovative elements for its products. However, it is still subject to debate whether these R&D investments always pay off. While prior research has confirmed that enhancing product innovativeness increases business performance in certain industries, corresponding findings for the video game market are lacking. This might be a result of missing theoretical conceptualizations and adequate empirical operationalizations of game innovativeness. Addressing this research gap, this study provides the first conceptualization and operationalization of game innovativeness, shedding first light on its performance effects. Based on longitudinal data on 351 computer games, our findings confirm that innovations in the game's presentation and principle enhance short-term success, whereas innovations in a game's storyline can be more of a hindrance than a godsend for companies. However, our results also show that performance effects of game innovativeness diminish over time.
Additional information: L86;O30
Keywords: 330; video games; product innovativeness; game innovativeness; innovation success; degree of newness